Changes in gray matter volume following electroconvulsive therapy in adolescent depression with suicidal ideation: A longitudinal structural magnetic resonance imaging study - Li, Xiao; Chen, Xiaolu; Yu, Renqiang; Dai, Linqi; Ai, Ming; Huang, Qian; Zhou, Yi; Chen, Wanjun; Guo, Jiamei; Zheng, Anhai; Kuang, Li (Frontiers in Psychiatry, 2022)
Abstract Objective: We aimed to investigate changes in whole brain grey matter volumes (GMVs) before and after ECT in adolescents with major depressive disorder (MDD) and suicidal ideation (SI). Methods: Thirty adolescents with MDD and SI were observed, structural magnetic resonance imaging (sMRI) were performed at baseline and after ECT for each patient. Compared 25 healthy controls (HCs) were scanned only at baseline. The voxel-based Morphometry (VBM) techniques were used to examine GMVs. Results: Compared with HCs, MDDs at baseline showed decreased GMVs in the left middle temporal gyrus, right superior temporal gyrus, right middle temporal gyrus, left precuneus, right precuneus and the left superior frontal gyrus. After ECT, MDDs showed increased GMVs in the right superior frontal gyrus and right superior temporal gyrus. Pearson correlation found that BSSI scores at baseline was negatively correlated with GMVs in the left superior frontal gyrus, and the HAMD and BSSI scores after ECT was negatively correlated with the GMVs in the right superior temporal gyrus. Conclusions: Frontal-temporal-precuneus structure changes may be a potential cause of depressive and suicidal symptoms in adolescents. ECT may improve depressive and suicidal symptoms in adolescents by regulating brain structures to compensate original defects.